Characterization of Linoleate 10-Hydratase of Lactobacillus plantarum and Novel Antifungal Metabolites - Chen, Yuan Y.; Liang, Nuan Y.; Curtis, Jonathan M.; Gänzle, Michael G. (Frontiers in Microbiology, 2016)
Lactobacilli convert linoleic acid to the antifungal compound 10-hydroxy-12-octadecenoic acid (10-HOE) by linoleate 10-hydratase (10-LAH). However, the effect of this conversion on cellularmembrane physiology and properties of the cell surface have not been demonstrated. Moreover, L. plantarum produces 13-hydroxy-9-octadecenoic acid (13-HOE) in addition to 10-HOE, but the antifungal activity of 13-HOE was unknown. Phylogenetic analyses conducted in this study did not differentiate between 10-LAH and linoleate 13-hydratase (13-LAH). Thus, linoleate hydratases (LAHs) must be characterized through their differences in their activities of linoleate conversion. Four genes encoding putative LAHs from lactobacilli were cloned, heterologous expressed, purified and identified as FAD-dependent 10-LAH. The unsaturated fatty acid substrates stimulated the growth of lactobacilli. We also investigated the role of 10-LAH in ethanol tolerance, membrane fluidity and hydrophobicity of cell surfaces in lactobacilli by disruption of 10-lah. Compared with the L. plantarum 10-lah deficient strain, 10-LAH in wild-type strain did not exert effect on cell survival and membrane fluidity under ethanol stress, but influenced the cell surface hydrophobicity. Moreover, deletion of 10-LAH in L. plantarum facilitated purification of 13-HOE and demonstration of its antifungal activity against Penicillium roquefortii and Aspergillus niger.